From ta to ha : elision of the alveolar stop in Singapore Mandarin - Sung, Chang Da (2019)
The third person pronoun in Singaporean Mandarin 他 ta undergoes instances of elision in speech. Aligning with previous studies, this elision, often part of syllable contraction is triggered by environments where the preceding morpheme is an object or a case marker. Co-articulation may also occur with the final of the previous syllable when an alveolar nasal is present. However, the presence of utterance initial elisions hints that the elision is no longer confined to environment triggered syllable contractions. That environmental frequency correlates with lower ratios of elision deserves more study. A matched guise study revealed that the variation does not index for any social group. The result suggests that the variation is more linguistically than socially motivated.